Consumer Online Knowledge-Sharing: Motivations and Outcome - Li, Yanhe; Li, Yanchen; Ma, Kunshu; Zhou, Xiu (Frontiers in Psychology, 2022)
As a new form of online reviews, Q&A reviews have been recently used by many e-commerce platforms to compensate for the weaknesses and problems related to trust and helpfulness found in traditional online reviews. This research documents what motivates people to share products or purchasing knowledge with others through Q&A reviews and why e-commerce platforms should place an emphasis on Q&A reviews. Importantly, our results provide evidence that, when receiving feedback (i.e., comments and likes), people are more likely willing to share knowledge with others and will have a higher level of loyalty. We believe that this study contributes to knowledge sharing and the e-commerce literature, and also has practical implications.